Redox potentials of high-valent iron-, cobalt-, and nickel-oxido complexes: evidence for exchange enhanced reactivity - Comba, Peter; Rensland, Anna-Maria; Pfaff, Florian Felix; Ray, Kallol (Israel journal of chemistry, 2020)
The ferrocene titration method has been employed to determine the one-electron reduction potentials of a series of oxido-iron(IV), oxido-cobalt(IV) and oxido/hydroxido-nickel(III) complexes based on the same tetradentate TMG3tren ligand (TMG3tren=tris[2-(N-tetramethylguanidyl)ethyl]amine). The S=2 ground state of the [(TMG3tren)FeIV=O]2+ complex allows an exchange enhanced reactivity, which enables it to perform efficient oxygen atom transfer (OAT) and hydrogen atom abstraction (HAA) reactions with a low one-electron reduction potential of 270 mV vs. SCE. In the absence of exchange enhanced reactivity, the OAT and HAA abilities of the S=3/2 [(TMG3tren)CoIV−O(Sc(OTf)3)]2+, S=1/2 [(TMG3tren)NiIII−O(H)]2+ and the previously reported S=1 [(TMC)(CH3CN)FeIV=O]2+ and [(N4Py)FeIV=O]2+ complexes can be directly correlated to their reduction potentials. Notably, [(N4Py)FeIV=O]2+ and [(TMG3tren)FeIV=O]2+ exhibit similar OAT and HAA reactivities although the reduction potential of [(N4Py)FeIV=O]2+ is 0.24 V more positive than that of [(TMG3tren)FeIV=O]2+. The present study therefore provides experimental evidence for exchange enhanced reactivity and rationalizes nature's choice for employing S=2 oxido-iron(IV) cores to achieve difficult oxidation reactions at biologically viable potentials.